PENGARUH FIRM SIZE, PROFITABILITY, DAN CEO DUALITY TERHADAP RISK DISCLOSURE - Via Novianty, Herlin Tundjung Setijaningsih (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to analyze the effect of firm size, profitability, and CEO duality of risk disclosure in listed banking companies in Indonesian Stock Exchange period 2016-2018. This research sample used 27 banking companies in Indonesian Stock Exchange during the period 2016-2018. This research uses the number of disclosure items in IFRS 7 in the index disclosed in each company’s annual report and also use multiple regression analysis. The results of this analysis indicate that firm size positively affect risk disclosure, while profitability and CEO duality have no impact on risk disclosure.